Theoretical Fundamentals of Improving the Investment Environment Attractive in Reducing Investment Risks - Shayakubov Shakhzod Shakabilovich; Ochilov Bobur Bakhtiyorovich (Zien Journals, 2022)
This article examines the essence of the attractiveness of the investment climate, the classical financial mechanisms for reducing investment risks, the views of foreign economists, the factors necessary to attract foreign investment and formulate scientific conclusions and recommendations to increase investment attractiveness.
Keywords: investment risks; classical financial mechanism; investment attractiveness; foreign investment